Hellenistic Roof Tiles in Jerusalem - Vukosavović, Filip; Cohen-Weinberger, Anat; Gadot, Yuval; Bocher, Efrat; Bejarano, Oscar; Shalev, Yiftah (Journal of Hellenistic Pottery and Material Culture, 2022)
Sixteen fragments of ceramic roof tiles, dated to the Hellenistic period in the late 2nd century BCE, were uncovered on the western slope of the City of David (Southeastern Ridge) during the Giv’ati Parking Lot excavations between 2017–2022. This is the earliest attestation for the use of roof tiles in the southern Levant, south of Beirut, and so far, it is the only attestation for their use in the region during the Hellenistic period. The petrographic analysis of the fragments shows that the tiles were manufactured with the locally available clay from the Moza Formation and that a specific recipe of raw materials adapted for the tiles was used. We suggest that the roof tiles were intended for the roofing of a building related to the Seleucid presence in the city at the time, the Hakra (Acra) being one such option.